STANDARDIZATION OF A TRADITIONAL POLYHERBO-MINERAL FORMULATION- BRAHMI VATI - mishra, amrita; Mishra, Arun K.; Ghosh, Ashoke K.; Jha, Shivesh (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The present study deals with standardization of an in-house standard preparation and three marketed samples of Brahmi vati, which is a traditional medicine known to be effective in mental disorders, convulsions, weak memory, high fever and hysteria. Preparation and standardization have been done by following modern scientific quality control procedures for raw material and the finished products. The scanning electron microscopic (SEM) analysis showed the reduction of metals and minerals (particle size range 2-5 μm) which indicates the proper preparation of bhasmas, the important ingredient of Brahmi vati. Findings of EDX analysis of all samples of Brahmi vati suggested the absence of Gold, an important constituent of Brahmi vati in two marketed samples. All the samples of Brahmi vati were subjected to quantitative estimation of Bacoside A (marker compound) by HPTLC technique. Extraction of the samples was done in methanol and the chromatograms were developed in Butanol: Glacial acetic acid: water (4.5:0.5:5 v/v) and detected at 225nm. The regression analysis of calibration plots of Bacoside A exhibited linear relationship in the concentration range of 50-300 ng, while the % recovery was found to be 96.06% w/w, thus proving the accuracy and precision of the analysis. The Bacoside A content in the in-house preparation was found to be higher than that of the commercial samples. The proposed HPTLC method was found to be rapid, simple and accurate for quantitative estimation of Bacoside A in different formulations. The results of this study could be used as a model data in the standardization of Brahmi vati.